Lo vostre humil fill, qui us desiga molt veure. Cartas del apotecario rosellonés Joan Pereta desde Valencia a su padre en Perpiñán (1474-1479). - ALMENAR FERNÁNDEZ, LUIS (Scripta)
In this article two personal letters are transcribed and studied. These were written by the apothecary Joan Pereta in the city of Valencia in 1474 and 1479, being sent to his father, the notary Jaume Pereta, to the town of Perpignan. The letters provide relevant information to reconstruct how information flows circulated at the end of the Late Middle Ages in the northwestern Mediterranean, as well as to investigate the personal and family history of Joan and Jaume Pereta. The language with which the letters were written also allows us to explore aspects of mentality, such as Joan's religious fervor and the relation of profound respect towards his father.